Chlorfenapyr ear tags to control Haematobia irritans (L.) (Diptera: Muscidae) on cattle - Guglielmone, Alberto Alejandro (2000)
The efficacy of ear tags containing 30% chlorfenapyr (total tag weight = 13 g) to control natural Haematobia irritans (L.) infestations was evaluated for Holstein heifers in Rafaela, province of Santa Fe, Argentina. A group of heifers (TG) was treated with two ear tags (one tag per ear). A control group (ACG) was maintained in a paddock adjacent to the TG paddock and, a distant control group (DCG) was maintained 700 m apart from the other groups. From day 4 to day 98 after treatment, H. irritans infestations of ACG were significantly higher (P < 0.05, test of Kruskal-Wallis) than the corresponding infestation of TG, but significantly lower than infestation in DCG, probably due to the proximity of TG. The chlorfenapyr control period, with an efficacy higher than 90% to reduce horn fly populations, lasted for 9 weeks when TG infestation was compared to fly numbers in ACG, but increased to 12 weeks in comparison to DCG. The results of this study show that ear tags impregnated with chlorfenapyr are a useful alternative to pyrethroids and organo-phosphate compounds for horn fly control. (C) 2000 Elsevier Science B.V.